The Nuclear Bulge extinction - Gosling, A; Blundell, K; Bandyopadhyay, R; Lucas, P (2008)
We present a new, high resolution (5" per pixel) near-infrared extinction map of the Nuclear Bulge using data from the UKIDSS-GPS. Using photometry from the J, H and K-bands we show that the extinction law parameter is also highly variable in this region on similar scales to the absolute extinction. We show that only when this extinction law variation is taken into account can the extinction be measured consistently at different wavelengths.